PERAN PENDIDIKAN ISLAM DALAM MENGEMBANGKAN ETIKA GURU MADRASAH IBTIDAIYAH YANG BERKUALITAS - Vindi Yunita Putri; Imron Fauzi; M. Ilmil Zawawi (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the role of Islamic education in strengthening the professional ethics of Madrasah Ibtidaiyah teachers. Using a literature review method, this research systematically examines books, scientific articles, regulations, and previous studies related to teacher ethics, professionalism, and the values of Islamic education. The findings show that Islamic education provides a strong moral foundation, such as trustworthiness, justice, responsibility, and exemplary behavior, which significantly shape the ethical conduct of teachers in carrying out their professional duties. Teachers who internalize these values are able to consistently apply ethical principles, build positive pedagogical relationships, and improve the quality of learning. The study also identifies several challenges, including teachers’ limited understanding of the code of ethics and the lack of institutional support in the form of ongoing training. These conditions indicate that strengthening teacher ethics requires spiritual development and structured institutional programs. Overall, the study concludes that Islamic education serves as a substantive and practical framework for enhancing teacher professionalism. Further research is recommended to use empirical approaches, such as qualitative studies or case studies, to provide a deeper depiction of the implementation of teacher ethic.